2016
DOI: 10.1123/jab.2015-0178
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Gait with Anteriorly Added Mass: A Pregnancy Simulation Study

Abstract: During pregnancy, the female body experiences structural changes, such as weight gain. As pregnancy advances, most of the additional mass is concentrated anteriorly on the lower trunk. The purpose of this study is to analyze kinematic and kinetic changes when load is added anteriorly to the trunk, simulating a physical change experienced during pregnancy. Twenty healthy females walked on a treadmill while wearing a custom made pseudo-pregnancy sac (1 kg) under three load conditions: sac only, 10 pound conditio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 23 publications
1
13
0
Order By: Relevance
“…Here, we present data from our laboratory collected on 44 healthy individuals [22 females (age: 22.9 ± 2.8 years (mean ± standard deviation (SD)), height: 1.63 ± 0.07 m, mass: 61.1 ± 8.5 kg) and 22 males (age: 24.9 ± 6.3 years, height: 1.78 ± 0.09 m, mass: 75.2 ± 14.2 kg)] while walking on an instrumented force treadmill (Bertec Corporation, Columbus, OH). Data were collected and processed using standard motion capture methodology which has been previously published (Ogamba et al, ). Individuals were tested walking at two walking speeds: self‐selected (∼1.27 m/s) and prescribed (1.25 m/s).…”
Section: Normal Structure Of the Human Pelvismentioning
confidence: 99%
“…Here, we present data from our laboratory collected on 44 healthy individuals [22 females (age: 22.9 ± 2.8 years (mean ± standard deviation (SD)), height: 1.63 ± 0.07 m, mass: 61.1 ± 8.5 kg) and 22 males (age: 24.9 ± 6.3 years, height: 1.78 ± 0.09 m, mass: 75.2 ± 14.2 kg)] while walking on an instrumented force treadmill (Bertec Corporation, Columbus, OH). Data were collected and processed using standard motion capture methodology which has been previously published (Ogamba et al, ). Individuals were tested walking at two walking speeds: self‐selected (∼1.27 m/s) and prescribed (1.25 m/s).…”
Section: Normal Structure Of the Human Pelvismentioning
confidence: 99%
“…The distribution of pressure sore areas of the control and experimental group is in accordance with our hypothesis that the special footwear redistributes the forces acting on the foot. During pregnancy, the increased loading on the forefoot described in the previous study (Karadag-Saygi et al, 2010;Ogamba et al, 2016) increases the forefoot pressure sore occurrence observed in Area 1 and 2 in the control group. The special footwear introduction in the experimental group led for the left foot to the increase in pressure sore occurrence at the edge of the heel probably associated with the plantar pressure redistribution more to the heel area as an increase in pressure sore occurrence in the forefoot areas was not signifi cant.…”
Section: Discussionmentioning
confidence: 54%
“…During pregnancy, the female body experiences structural changes, such as weight gain. As pregnancy advances, most of the additional mass is concentrated interiorly on the lower trunk [50] . In such conditions increase in the load with the increase in joint movements increases stress on the musculoskeletal system and contribute to pain [51] .…”
Section: Size and Number Of Base Of Supportmentioning
confidence: 99%